2006
DOI: 10.1007/s11534-005-0009-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of TiO2 thin films by micro-Raman spectroscopy

Abstract: Abstract:The Raman spectroscopy method was used for structural characterization of TiO 2 thin films prepared by atomic layer deposition (ALD) and pulsed laser deposition (PLD) on fused silica and single-crystal silicon and sapphire substrates. Using ALD, anatase thin films were grown on silica and silicon substrates at temperatures 125-425 • C. At higher deposition temperatures, mixed anatase and rutile phases grew on these substrates. Post-growth annealing resulted in anatase-to-rutile phase transitions at 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 37 publications
8
26
0
Order By: Relevance
“…No typical rutile peaks were seen even at this relatively high annealing temperature. Indeed, it is reported that no structural transformation to other crystalline phases of ALD TiO 2 for temperatures up to 700 C in air and a sudden change to rutile happened at 750 C. 18 Considering the small roughness and the similar XRD pattern that the annealed TiO 2 has, smooth and high quality TiO 2 MEMS devices can thus be made by this "low temperature deposit and then anneal" method.…”
Section: A Surface Roughness and Crystallizationmentioning
confidence: 95%
“…No typical rutile peaks were seen even at this relatively high annealing temperature. Indeed, it is reported that no structural transformation to other crystalline phases of ALD TiO 2 for temperatures up to 700 C in air and a sudden change to rutile happened at 750 C. 18 Considering the small roughness and the similar XRD pattern that the annealed TiO 2 has, smooth and high quality TiO 2 MEMS devices can thus be made by this "low temperature deposit and then anneal" method.…”
Section: A Surface Roughness and Crystallizationmentioning
confidence: 95%
“…Besides, higher amounts of crystalline phases can be obtained in annealed films [35,36]. At annealing temperatures lower than 700°C, the crystallization to anatase and at higher temperatures the anatase-to-rutile transformation may proceed [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, higher amounts of crystalline phases can be obtained in annealed films [35,36]. At annealing temperatures lower than 700°C, the crystallization to anatase and at higher temperatures the anatase-to-rutile transformation may proceed [36,37]. The impact of postdeposition annealing may depend in certain extent on the phase composition [36] as well as concentration and type of impurities in as-grown films [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Ti and TiN-a plates, broad peaks were observed at around 200-400 and 600 cm −1 , which can be assigned to the amorphous titania formed on the plate surface [24][25][26]. The rutile peaks clearly appeared in the spectra of these plates after heating and their relative intensity increased with an increase in the temperature.…”
Section: Formation Of Titania By Oxidizing Titanium Nitride Phasementioning
confidence: 96%